2017
DOI: 10.1590/1807-1929/agriambi.v21n1p21-26
|View full text |Cite
|
Sign up to set email alerts
|

Response of eggplant crop fertigated with doses of nitrogen and potassium

Abstract: A B S T R A C TThe objective of the present study was to evaluate the response of eggplant, cv. 'Ciça' , with respect to yield, number of fruits and dry matter (root and stem), when grown in a greenhouse and conducted under fertigation with nitrogen and potassium. Resposta da cultura da berinjela fertirrigada com doses de nitrogênio e potássio R E S U M O Objetivou-se, no presente estudo, avaliar a resposta da cultura da berinjela, cultivar Ciça, com relação à produtividade, número de frutos e massa seca (raiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 13 publications
1
18
0
10
Order By: Relevance
“…Akintomide and Osundare (2015) also reported a significant response of okra LA with N fertilization. Other authors like, Souza et al (2016), and Souza et al (2017) observed positive responses of N fertilization on the LA of several agricultural crops.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Akintomide and Osundare (2015) also reported a significant response of okra LA with N fertilization. Other authors like, Souza et al (2016), and Souza et al (2017) observed positive responses of N fertilization on the LA of several agricultural crops.…”
Section: Resultsmentioning
confidence: 83%
“…The minimum LA observed in the absence of N may be attributed to the poor nutritional status of the plants subjected to this treatment, which has resulted in delayed leaf expansion (Olaniyi et al, 2010;Souza et al, 2016;Zubairu et al, 2017). The positive effect of N on LA is related to the functions performed by this nutrient on the development of cultures, since this element helps in cell division and stretching; it plays an important role in chlorophyll, protein, nucleic acid, hormones, and synthesis of vitamins (Omotoso & Shittu, 2007;Akande et al, 2010;Souza et al, 2017). In addition, it was found that LA responds positively to this element when supplied in adequate quantity .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Com exceção do K para a eficiência do uso da água e N para a concentração interna de CO 2 , todos os outros parâmetros de trocas gasosas apresentaram diferenças significativas para as doses de K e N. Houve interação entre as doses de N e K para fotossíntese, condutância estomática, transpiração e eficiência instantânea de carboxilação. Os maiores valores para fotossíntese líquida, condutância estomática, transpiração, eficiência de carboxilação instantânea e matéria seca total foram encontrados na faixa de 125-185 kg ha -1 de K e 215-268 kg ha -1 de N. Souza et al 2017), the physiological responses of eggplants under K and N doses have not been well documented. The photosynthesis, transpiration, stomatal conductance and internal CO 2 concentration may be used to diagnose physiological alterations in plants submitted to adverse conditions (Andrade Junior et al 2011).…”
Section: Introductionunclassified